Bone regenerative medicine: metatarsus defects in sheep to evaluate new therapeutic strategies for human long bone defect. A systematic review. Issue 7 (July 2020) - Veronesi, Francesca; Martini, Lucia; Giavaresi, Gianluca; Fini, Milena
Highlights: Large bone defects are difficult to treat. Autografts and allografts show disadvantages and are replaced by scaffolds. The review identify scaffolds for large bone regeneration through in vivo studies performed in sheep metatarsus defects. Natural, synthetic or hybrid scaffolds were employed in the 11 in vivo studies identified from 2000 to 2019. Abstract: Introduction: Large bone defects in long bone are not able to repair themselves and require grafts. Although autograft is the gold standard, it is associated with some disadvantages. Consequently, the application of tissue engineering (TE) techniques help with the use of allogenic biological and artificial scaffolds, cells and growth factors (GFs). Following 3Rs and in vitro testing strategies, animal models are required in preclinical in vivo studies to evaluate the therapeutic effects of the most promising TE techniques. Materials and methods: A systematic review was performed from 2000 to 2019 to evaluate bone regeneration sheep metatarsus defects. Results: Eleven in vivo studies on sheep metatarsus defect were retrieved. The mid-diaphysis of metatarsus was the region most employed to perform critical size defects. Natural, synthetic and hybrid scaffolds were implanted, combined with bone marrow mesenchymal stem cells (BMSCs), GFs such as osteogenic protein 1 (OP1) and platelet rich plasma (PRP). The maximum follow-up period was 4 and 6 months in which radiography, histology, histomorphometry, computed tomography (CT) and biomechanics were performed to evaluate the healing status. Conclusions: the sheep metatarsus defect model seems to be a suitable environment with a good marriage of biological and biomechanical properties. Defects of 3 cm are treated with natural scaffolds (homologous graft or allografts), those of 2.5 cm with natural, synthetic or composite scaffolds, while little defects (0.5 × 0.5 cm) with composite scaffolds. No difference in results is found regardless of the defect size.